Manufacturing and characterization of novel clutch non-conventional fiber-reinforced composite laminates. (1st May 2019) - Vakili Rad, Cyrus; Thomas, Frank D.; Seay, Brandon; van Tooren, Michael J.L.; Sockalingam, Subramani
Abstract: In this study the manufacture and characterization of novel non-conventional composite laminates coined as clutch laminates are presented. These carbon/epoxy laminates are manufactured using prepreg slit tape in an automated fiber placement (AFP) machine through tow skips. The AFP process allows for the tailoring of material architecture, resulting in woven-like structures without the need for a loom. These laminates are heterogeneous due to variation of fiber orientation and therefore, the material properties at a given section is a function of in-plane spatial coordinates. The thermal and mechanical behavior is studied where the clutch laminate lay-up pattern is represented with a sub cell approach utilizing 3D shell finite elements where the tows are deposited onto the regions mimicking the AFP course. Experimental results show that post-cure thermal warpage for the clutch carbon/epoxy laminates is significantly reduced when compared to conventional asymmetric laminates while also exhibiting tensile properties comparable to traditional laminates of the same ply counts. Based on the model predictions, the reduction in the warpage is attributed to the spatial variations in the local stacking sequences leading to reduced net deformation.